Transmission of Local and Traditional Music in Indonesian Popular Music (Case Studies of Indonesian Music Groups) - Sosrowijaya, Kerso Manungga (Harmonia : Journal of Music and Arts, 2023)
This article explores the dynamic process of transmitting local and traditional music within the context of Indonesian popular music. As Indonesia boasts a rich cultural heritage, the study delves into how traditional musical elements are incorporated and transformed within the works of contemporary Indonesian music groups. The research employs a qualitative approach, utilizing case studies of prominent Indonesian music groups. Through an in-depth analysis of their compositions, arrangements, and performances, the study aims to unravel how traditional musical influences are transmitted and integrated into the fabric of popular music. The findings reveal diverse strategies Indonesian music groups employ in incorporating local and traditional elements. Case studies showcase the adaptation of traditional instruments, melodic patterns, and rhythmic structures, providing insight into how cultural heritage is woven into the contemporary musical landscape. The discussion section engages with the implications of this transmission process, addressing questions of cultural identity, artistic innovation, and audience reception. It explores how the synthesis of traditional and popular music contributes to the evolution of Indonesia's musical identity and its resonance within a global context. In conclusion, this article illuminates the multifaceted nature of the transmission of local and traditional music in Indonesian popular music. The case studies provide a lens to understand the dynamic interplay between tradition and innovation, shedding light on the creative processes that shape the country's musical tapestry. This study contributes to the broader discourse on the global dynamics of music transmission and the significance of cultural heritage in contemporary musical expressions.